2010
DOI: 10.4271/2010-01-0794
|View full text |Cite
|
Sign up to set email alerts
|

(Particle) Emissions of Small 2- & amp; 4-Stroke Scooters with (Hydrous) Ethanol Blends

Abstract: The objectives of the present work are to investigate the regulated and unregulated (particle) emissions of a classical and modern 2-stroke and a typical 4-stroke scooter with different ethanol blend fuels. There is also comparison of two different ethanol fuels: pure ethanol (E) *) and hydrous ethanol (EH) which contains 3.9% water and is denatured with 1.5% gasoline. Special attention is paid in this research to the hydrous ethanol, since the production costs of hydrous ethanol are much less than those for (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Rijkeboer et al (2005) also showed a nucleation mode with CMD of about 30 nm and an accumulation mode with CMD of about 100 nm. In contrast, Czerwinski et al (2010) and Etissa et al (2008) found a single mode size distribution for their evaluated 2-stroke two wheelers. It is important to note that in all of these studies the size distributions have been measured at steady state test conditions.…”
Section: Real Time Size Distributionsmentioning
confidence: 62%
See 1 more Smart Citation
“…Rijkeboer et al (2005) also showed a nucleation mode with CMD of about 30 nm and an accumulation mode with CMD of about 100 nm. In contrast, Czerwinski et al (2010) and Etissa et al (2008) found a single mode size distribution for their evaluated 2-stroke two wheelers. It is important to note that in all of these studies the size distributions have been measured at steady state test conditions.…”
Section: Real Time Size Distributionsmentioning
confidence: 62%
“…They also measured the particle mass distribution for some of the motorcycles using a micro orifice uniform deposit impactor (MOUDI). Czerwinski et al (2003Czerwinski et al ( , 2006Czerwinski et al ( , 2010 have conducted several studies on two wheelers during the research programs of the Swiss Federal Office of Environment Forests and Landscape (FOEFL). They employed a scanning mobility particle sizer (SMPS) to report the count distribution of particles over steady-state driving conditions (mostly 40 km/hr).…”
Section: Introductionmentioning
confidence: 99%
“…The relative contribution of mopeds and motorcycles to PM emissions started to increase as the levels from other vehicles started to decrease. The particulate emissions of two-stroke PTW have been studied by many researchers (e.g., references [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]) exceeding 100 mg/km and 10 13 p/km in most cases. Two-stroke mopeds emit significant amounts of aromatic volatile organic compounds and also produce significant secondary organic aerosol [9,34].…”
Section: Introductionmentioning
confidence: 99%
“…Two-stroke mopeds emit significant amounts of aromatic volatile organic compounds and also produce significant secondary organic aerosol [9,34]. Four-stroke mopeds [26,27,33,34,38,39] and motorcycles [23,29,[35][36][37][40][41][42][43] have generally lower SPN emissions, but in most cases above the limit applicable for passenger cars. Data for the latest Euro 4 PTW are limited (e.g., reference [44]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation